Unraveling the Molecular Nexus between GPCRs, ERS, and EMT - Niti Kumari; Somrudee Reabroi; Brian J. North (Mediators of Inflammation)
G protein-coupled receptors (GPCRs) represent a large family of transmembrane proteins that transduce an external stimulus into a variety of cellular responses. They play a critical role in various pathological conditions in humans, including cancer, by regulating a number of key processes involved in tumor formation and progression. The epithelial-mesenchymal transition (EMT) is a fundamental process in promoting cancer cell invasion and tumor dissemination leading to metastasis, an often intractable state of the disease. Uncontrolled proliferation and persistent metabolism of cancer cells also induce oxidative stress, hypoxia, and depletion of growth factors and nutrients. These disturbances lead to the accumulation of misfolded proteins in the endoplasmic reticulum (ER) and induce a cellular condition called ER stress (ERS) which is counteracted by activation of the unfolded protein response (UPR). Many GPCRs modulate ERS and UPR signaling via ERS sensors, IRE1α, PERK, and ATF6, to support cancer cell survival and inhibit cell death. By regulating downstream signaling pathways such as NF-κB, MAPK/ERK, PI3K/AKT, TGF-β, and Wnt/β-catenin, GPCRs also upregulate mesenchymal transcription factors including Snail, ZEB, and Twist superfamilies which regulate cell polarity, cytoskeleton remodeling, migration, and invasion. Likewise, ERS-induced UPR upregulates gene transcription and expression of proteins related to EMT enhancing tumor aggressiveness. Though GPCRs are attractive therapeutic targets in cancer biology, much less is known about their roles in regulating ERS and EMT. Here, we will discuss the interplay in GPCR-ERS linked to the EMT process of cancer cells, with a particular focus on oncogenes and molecular signaling pathways.